2009
DOI: 10.1002/tax.581016
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and evolution of the Arctium‐Cousinia complex (Compositae, Cardueae‐Carduinae)

Abstract: These authors contributed equally to this publicationThe phylogeny and evolution of the Arctium-Cousinia complex, including Arctium, Cousinia as one of the largest genera of Asteraceae, Hypacanthium and Schmalhausenia, is investigated. This group of genera has its highest diversity in the Irano-Turanian region and the mountains of Central Asia. We generated ITS and rpS4-trnT-trnL sequences for altogether 138 species, including 129 (of ca. 600) species of Cousinia. As found in previous analyses, Cousinia is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 79 publications
7
51
0
Order By: Relevance
“…Within Carduinae, the close relationship of Shangwua and Xeranthemum was supported by our analysis and recent studies (Wang et al, ; Wang et al, ). The close relationships of Cousinia + ( Arctium + Schmalhausenia ) and Aucklandia + Frolovia , previously inferred by López‐Vinyallonga et al () and Wang et al (), separately, were also supported in our phylogenetic inferences (PP > 0.95; Fig. B).…”
Section: Discussionsupporting
confidence: 87%
“…Within Carduinae, the close relationship of Shangwua and Xeranthemum was supported by our analysis and recent studies (Wang et al, ; Wang et al, ). The close relationships of Cousinia + ( Arctium + Schmalhausenia ) and Aucklandia + Frolovia , previously inferred by López‐Vinyallonga et al () and Wang et al (), separately, were also supported in our phylogenetic inferences (PP > 0.95; Fig. B).…”
Section: Discussionsupporting
confidence: 87%
“…However, the complete absence of polyploid chromosome numbers among the 149 species analyzed of the Arctium-Cousinia complex (Watanabe 2002) implies that (allo-)polyploid speciation did not play a role in the evolution of this complex (López-Vinyallonga et al 2009). …”
Section: Discussionmentioning
confidence: 96%
“…We have found little correspondence between phylogeny and karyology by mapping the chromosome number data for the 63 species present in the Bayesian phylogenetic tree by López-Vinyallonga et al (2009) for which chromosome numbers have been reported (Fig. 3).…”
Section: Hypacanthodesmentioning
confidence: 93%
See 2 more Smart Citations